Perturbation and error analyses of partitioned LU factorization for block tridiagonal linear systems - Huang, Ting-Zhu; Wu Chi-Yе (Ukrains’kyi Matematychnyi Zhurnal, 2016)
The perturbation and backward error analyses of the partitioned LU factorization for block tridiagonal matrices are presented. Moreover, we consider the perturbation bounds for the partitioned LU factorization for block tridiagonal linear systems. Finally, numerical examples are given to verify our results.